1981
DOI: 10.1037/0033-2909.89.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Time and method in coaching for the SAT.

Abstract: A review of studies of coaching for the Scholastic Aptitude Test (SAT) indicates that, although there are methodological flaws, some definite regularities emerge relating the size of score effects associated with coaching to the amount of student contact time entailed in the coaching programs. Rank-order correlations between these 2 variables were upwards of .7 for both SAT-Verbal (SAT-V) and SAT-Mathematics (SAT-M) scales. The relationship was nonlinear with arithmetically increasing amounts of score effect a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 17 publications
8
105
4
Order By: Relevance
“…That is, it is unlikely that g is so malleable as to be enhanced by simple practice (Messick & Jungeblut, 1981), especially given that intensive long-term intervention programs do not appear to have any lasting effects on measured intelligence (Jensen, 1998;Spitz, …”
Section: Three Explanations Of Retest Effects and Theirmentioning
confidence: 99%
“…That is, it is unlikely that g is so malleable as to be enhanced by simple practice (Messick & Jungeblut, 1981), especially given that intensive long-term intervention programs do not appear to have any lasting effects on measured intelligence (Jensen, 1998;Spitz, …”
Section: Three Explanations Of Retest Effects and Theirmentioning
confidence: 99%
“…In their efforts to develop measures of various traits, ETS researchers have examined many potential sources of irrelevant variance, including anxiety (French 1962;Powers 1988Powers , 2001, response styles (Damarin and Messick 1965), coaching (Messick 1981b(Messick , 1982aMessick and Jungeblut 1981), and stereotype threat (Stricker 2008;Stricker and Bejar 2004;Stricker and Ward 2004). Messick (1975Messick ( , 1989 made the evaluation of plausible sources of irrelevant variance a cornerstone of validation, and he made the evaluation of construct-irrelevant variance and construct underrepresentation central concerns in his unified model of validity.…”
Section: Controlling Irrelevant Variancementioning
confidence: 99%
“…He published these results in the form of a meta-analysis (Messick and Jungeblut 1981), in which the authors noted "definite regularities" (p. 191) between SAT coaching effects and the amount of student contact time in coaching programs. On this basis, Messick and Jungeblut concluded that the size of the effects being claimed by coaching companies could probably be obtained only with programs that were tantamount to full-time schooling.…”
Section: Extending Lessons Learnedmentioning
confidence: 99%